The answer is a² + 6. "Sum of a squared and 6" means you square a value and then add 6 to it.
Answer: 7
Step-by-step explanation:
Step 1: Subtract 3 from both sides.
6a+3−3=45−3
6a=42
Step 2: Divide both sides by 6.
6a
/6
=
42
/6
1. Expand
2x − 2 + 4 = 4x + 4
2. Simply
2x + 2 = 4x + 4
3. Subtract
2 = 4x + 4 - 2x
4. Simplify
2 = 2x + 4
5.Subtract
2 - 4 = 2x
6. Simplify
-2 = 2x
7. Divide both sides by
-1 = x
8.Switch sides.
x = -1
Answer:
-t = -8 ×5
-t = -40
t= 40
good luck have a nice day
Answer:
350
Step-by-step explanation: